(untitled) (Polish Yearbook of International Law, 2023)
The article takes the renewed demands of the Polish government as an opportunity to examine the question of whether Germany is obliged to pay reparations to Poland. Based on an analysis of the international agreements concluded since 1945, it can be shown that the Polish government’s demands on Germany are unfounded.